Prevenção primária de abuso sexual : avaliação da eficácia de um programa com adolescentes e pré-adolescentes em ambiente escolar. - Padilha, Maria da Graça Saldanha (Universidade Federal de São Carlos, 2007)
This study was aimed at evaluating the efficacy of a child sexual abuse primary prevention program conducted in the school setting. The first part of the study was aimed at verifying low-income parents' conceptions about child sexual abuse. Sixtythree parents residents of the school's community where the prevention program was done participated of the study. Participants answered a Questionnaire on Child Abuse Conceptions. Results showed that parents where knowledgeable about child sexual abuse, although some of their conceptions could be altered to increase their child protection of at risk situations repertoire. The second part of the study had as a goal to evaluate a child sexual abuse primary prevention program in the school setting of the same community involved in the initial part of the study. Sixty two grade 6 students (30 female and 32 male) of a rural community in the Metropolitan area of Curitiba, Paraná participated o the intervention. The second part of the study had the following sequence: a Pre-Test (conducted one week prior to the intervention), Intervention (12 weekly sessions), a Post-Test (after the intervention), and a Follow-up (conducted 18 months after the program). A Questionnaire on Child Sexual Abuse was given in three of the occasions mentioned above. The 10 intervention sessions of one-and-a-half hour each involved social skills training, discussions on sexuality, discrimination of abusive situations, and self-protection skills training. The repertoire to be installed involved discrimination of risk, responding in an assertive way to the offender, leaving the situation and reporting it to a reliable adult. Analysis of students´ group performance in the three phases of the study indicated an increase after the intervention, which was maintained after 18 months, although with a small decrease. Of the four factors measured by the Questionnaire knowledge on sexual abuse, discrimination of at risk situations, saying no , and leaving the situation quickly, and reporting the abuse to a reliable adult the factor on sexual abuse knowledge had significant increases in Post- Test and Follow-Up. General performance was significantly different, pointing out to the efficacy of the intervention as measured by the Questionnaire. In general, data seems to indicate an improvement in students´ repertoire of self-protective skills in situations at risk of child sexual abuse. The promising results point out to the feasibility of school prevention of child sexual abuse in the school setting.
Keywords: Crianças - abuso e negligência; Abuso sexual prevenção; Infância; Adolescência; Escola; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL